Enhancement of the dynamic bandwidth channel access for IEEE 802.11ac WLANs. (5th September 2019) - Halfaoui, Fadhila; Yazid, Mohand; Medjkoune-Bouallouche, Louiza
The new IEEE 802.11ac amendment aim is to significantly increase the throughput within the Basic Service Set (BSS) by improving physical data rate. IEEE802.11ac provides at least 1 Gbps for Multi-Station (Multi-STA) and 500 Mbps for single link. This achieved throughput is obtained by adding many enhancements for PHY and MAC layers. One of the main features that allows 802.11ac to reach gigabit transmission rates is static and dynamic channel bonding technique. In this paper, we first overview the static 80 MHz and the dynamic 20/40/80 MHz channel access schemes that are defined in 802.11ac. Then, we present the proposed enhancement of the dynamic access for an 80 MHz wide channel. The simulation results show that the enhanced dynamic access offers better throughput compared to the two methods used by 802.11ac stations.